Rancangan Aplikasi Agenda dengan Fitur Push Notification dan Reminder Berbasis Android Studi Kasus pada Kantor Kejaksaan Negeri Jakarta Selatan (Yayasan Kawanad, 2023)
This research aims to develop an Android-based agenda application with push notification and reminder features to support activity management in the Civil Law and State Administration Sector of the South Jakarta District Attorney's Office. Currently, management of the activity agenda is still done manually, causing frequent forgetting regarding the schedule that will or is currently taking place. Through an application development approach, this research creates an effective solution in the form of an agenda application that provides notifications on mobile devices when there is a new agenda or schedule in progress. This application is based on Android, uses the Java programming language, XML as the user interface, and integrates Firebase technology, such as Firebase Notification, Firebase Cloud Messaging, and Firebase Realtime Database. It is hoped that the results of this research will make it easier for employees and prosecutors to access and manage information regarding activity schedules, as well as provide automatic reminders. By implementing this application, it is hoped that the performance of the South Jakarta District Prosecutor's Office can be more efficient in carrying out its duties and functions, while the publication of this system can be an effective means of conveying information to all employees.